2015
DOI: 10.1039/c5ra00035a
|View full text |Cite
|
Sign up to set email alerts
|

Comparative supercapacitance performance of CuO nanostructures for energy storage device applications

Abstract: (a)–(c) FE-SEM images of CuO nanoplates on Ni foam, flower-shaped CuO and bud-shaped CuO. (d) Specific capacitance and (d) and (e) Ragone plots of power density vs. energy density according to CuO electrodes in an asymmetrical device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(56 citation statements)
references
References 41 publications
6
50
0
Order By: Relevance
“…The XRD patterns of the CuO-TiO 2 NT catalysts with a Cu content larger than 5 wt % (Figure 4a and Figure S1) exhibit diffraction peaks at 35.5 • (−111) and 38.6 • (111), characteristic of CuO phase in correlation with the reference pattern of tenorite CuO (Card JCPDS No. 00-001-1117) and that reported in the literature for monoclinic phase CuO [26][27][28]. The strong diffraction peaks of all samples indicate the purity and high crystalline nature of the TiO 2 and CuO phases in the different xCuO-TiO 2 NT catalysts.…”
Section: The Crystal Structure and Thermal Stabilitysupporting
confidence: 49%
See 1 more Smart Citation
“…The XRD patterns of the CuO-TiO 2 NT catalysts with a Cu content larger than 5 wt % (Figure 4a and Figure S1) exhibit diffraction peaks at 35.5 • (−111) and 38.6 • (111), characteristic of CuO phase in correlation with the reference pattern of tenorite CuO (Card JCPDS No. 00-001-1117) and that reported in the literature for monoclinic phase CuO [26][27][28]. The strong diffraction peaks of all samples indicate the purity and high crystalline nature of the TiO 2 and CuO phases in the different xCuO-TiO 2 NT catalysts.…”
Section: The Crystal Structure and Thermal Stabilitysupporting
confidence: 49%
“…The increased heating tolerance of the TiO 2 nanotubes modified with CuO nanoparticles can be attributed to the reduction of the total number of OH groups hydrated in the interlayers of the TiO 2 NTs, since Cu is hydrated with fewer OH groups relative to those hydrated at the Ti surface [31]. [26][27][28]. The strong diffraction peaks of all samples indicate the purity and high crystalline nature of the TiO2 and CuO phases in the different xCuO-TiO2 NT catalysts.…”
Section: The Crystal Structure and Thermal Stabilitymentioning
confidence: 91%
“…Copper oxides have been extensively studied in energy storage devices including supercapacitors and lithium‐ion batteries, because of their ease of preparation, low environmental impact and high electrochemical activity . In order to improve the electrode's performance, self‐supported materials have been created by directly growing the active material on the surface of the current collector ,.…”
Section: Introductionmentioning
confidence: 99%
“…21 Furthermore, these nanostructures can be easily converted to CuO 20,22,23 which is known as a p-type semiconductor with a narrow indirect bandgap of 1.2-1.5 eV at room temperature (RT), 24,25 with variety of applications in sensors, solar cells, Li-ion battery electrodes 26,27 and supercapacitors. [28][29][30][31][32] CuO as a supercapacitor electrode has speci¯c capacitance in the range of 100-620 F/g. 30,32 The recent studies have shown that metal hydroxides materials are prone to deliver better capacitance than metal oxides due to higher stability especially in alkaline solutions.…”
Section: Introductionmentioning
confidence: 99%